Society 5.0; Tuntutan Strategi Pendidikan Entrepreneurship di Pesantren Melalui SOAR Analysis - Moch Shohib; Narsim (Idarotuna : Journal of Administrative Science, 2022)
Santripreneur is a program of Islamic education transformation in Islamic boarding schools. The contribution of this research is the contribution of thought in developing the santripreneur program of pesantren in the industrial era of society which requires educational innovation in the community to equip generations with hard skills and soft skills. Islamic boarding schools respond to developments by reforming both in terms of learning methods, materials taught and adding pesantren programs without losing the identity of the real pesantren to create the output of pesantren who are ready to contribute to the economic development of the society era. This study discusses how to implementation model of the santripreneur program in Islamic boarding schools. Researchers used descriptive qualitative research methods, researchers used data analysis with four stages. Data collection, data condensation, data presentation and conclusion verification. The results of the study showed the transformation of Islamic education in Islamic boarding schools does not eliminate the dignity of Islamic boarding schools that have long been embedded. The santripreneur program becomes a forum for students' creativity in designing a product and entrepreneurship as in Islamic rules that are taught in Islamic boarding schools. The pesantren's santripreneur program is able to provide students to be open minded, productive and innovative thinking and the ability to adapt in the industrial world. Meanwhile, the students' hard skills are analytical skills, using social media, and the ability to promote the products in the society era.